c/o Haus Lange - Haus Esters 1984-1999 - Heynen, Julian; Storck, Gerhard (Krefeld : Kaiser Wilhelm Museum, 1999)
Balka, Miroslaw ; Berger, Ralf ; Bleckner, Ross ; Brandl, Herbert ; Bustamante, Jean-Marc ; Caramelle, Ernst ; Cragg, Tony (Anthony) ; Daniels, René ; Deacon, Richard ; de Cordier, Thierry ; Dorner, Helmut ; Douglas, Stan ; Eichhorn, Maria ; Förg, Gunther ; Fritsch, Katharina ; Gerdes, Ludger ; Goldstein, Zvi ; Gonzalez-Foerster, Dominique ; Graham, Rodney ; Gursky, Andreas ; Halley, Peter ; Hauch, Thierry ; Hohenbüchler, Christine & Irene ; Huws, Bethan ; Kiecol, Hubert ; Klingelhöller, Harald ; Lemieux, Annette ; Lord, Andrew ; Luy, Wolfgang ; McCollum, Allan ; Mucha, Reinhard ; Muñoz, Juan ; Ruff, Thomas ; Scanlan, Joe ; Schneider, Gregor ; Schütte, Thomas ; Slominski, Andreas ; Stadtbäumer, Pia ; Struth, Thomas ; Trockel, Rosemarie ; Tuymans, Luc ; Vercruysse, Jan ; Vermeiren, Didier ; Wall, Jeff ; West, Franz ; Wiitasalo, Shirley
Anlässlich der Ausstellung "am Horizont", die vom 21.11.1999 bis 27.2.2000 im Kaiser Wilhelm Museum Krefeld gezeigt wird.
Duits
boek